Mirtron-mediated RNA knockdown/replacement therapy for the treatment of dominant retinitis pigmentosa - Harry O. Orlans (Nature Portfolio, 2021)
Rhodopsin-related dominant retinitis pigmentosa is a degenerative disease of the retina of the eye for which there is no current treatment. In this study, the authors use a novel form of RNA-interference- artificial mirtrons- to slow retinal degeneration in a mouse model of the disease.